Assessing the Impact of Epidural Analgesia Early Pain Management and Functional Outcomes Following Deformity Surgery: A Retrospective Review. (1st September 2019) - Adeyemo, Emmanuel; Barrie, Umaru; Nguyen, Madelina; Elguindy, Mahmoud; Dosselman, Luke; Hall, Kristen M; Moreno, Jessica R; Bagley, Carlos A
Abstract: INTRODUCTION: ERAS is a multifaceted, multidisciplinary approach for patients undergoing surgery with the aim of improving patient functional recovery while shortening postop hospital length of stay and reducing readmission rates. ERAS has emerged as an instrumental strategy for improving the quality and value of surgical care and has been shown to reduce healthcare costs and improve patients' overall satisfaction. ERAS achieves its goals through a multidisciplinary approach, integrating the best practices from multiple healthcare fields into a standardized protocol. These protocols form an integrated continuum of care with 3 broad stages: preparing patients for surgery, reducing the impact of surgery, and enabling faster recovery for patients. Importantly, an essential component of ERAS is effective pain management. Here, we retrospectively assessed the efficacy of ERAS implementation for spinal deformity correction surgery patients at UT Southwestern. METHODS: The records of 59 patients who had undergone corrective deformity surgery and were given epidural analgesia as the primary method of early pain control were reviewed. Baseline characteristics such as age, body mass index (BMI), and number of segments fused were evenly matched. Postoperative parameters including distance in physical therapy, length of hospital stay, visual analog scale (VAS) pain scores, number of readmissions, and postoperative complications were compared and contrasted. RESULTS: Pain scores were significantly reduced by POD 5 following implementation of ERAS (4.15 vs 2.08, P  = .021). Furthermore, ERAS patients achieved higher average ambulatory distance on PODs 5 (259 vs 273), 6 (426.2 vs 528.2), and 7 (424.9 vs 577.5). The amount of blood loss was significantly lower in the ERAS group when compared to the non-ERAS group (1772.73 vs 11168.36, P -value = .007). The ERAS group required less supplemental opioids when compared to the non-ERAS group. CONCLUSION: Implementation of a standardized ERAS protocol for spinal-corrective deformity surgery reduced postoperative pain, improved early patient functional recovery, and decreased patient opioid usage.